King David - Penny Frank; Tony Morris (UK USA Lion Publishing, 1987)
Retells some of the adventures of the shepherd boy David before he became King of Israel.
col. ill.
Australia
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Jews -- Kings and rulers -- Biography -- Juvenile literature; Theology; Bible stories, English -- Old Testament; Bible stories -- Old Testament